Faktor Strategi Koping pada Pasien Kanker yang Menjalani Kemoterapi - Maria Evarista Sugo; Tiyas Kusumaningrum; Rista Fauziningtyas (Universitas Airlangga, 2019)
Introduction: Chemotherapy is one of the treatments for cancer that is effective and requires a considerable amount of time so that an adaptive coping strategy is needed from the patient. Patient coping strategies can be influenced by physical, psychological, and social factors. The purpose of this study was to analyze the factors associated with coping strategies for cancer patients undergoing chemotherapy at Prof. W Z Johannes Kupang Hospital.Methods: The design in this study was cross-sectional. The total population were 163 and obtained 100 respondents by consequtive sampling. Independent variables were physical condition, emotional atmosphere, self-concept, and family support. The dependent variable was the coping strategy of cancer patients who undergo chemotherapy. The instrument used The Chemotheraphy Symptom Assessment Scale (C-SAS), Emotional Regulation Questionnaire (ERQ), self-concept, family support and The Cancer Coping Questionnaire. Data were analyzed with Spearman's Rho, and Pearson.Results: There is a relationship between physical condition (p=0.030), emotional condition (p=0.001), self-concept (p=0,000), family support (p=0,000) with coping strategies for cancer patients who undergo chemotherapy.Conclusion: Coping strategies in patients undergoing cancer can be affected by physical conditions while undergoing chemotherapy, psychological experienced by patients, and social support that can come from family and close relatives. Nurses who were close to patients during the chemotherapy process can also be a support system so that patients' coping strategies can be adaptive during chemotherapy.